A comparative study of bioprocess performance for improvement of bioethanol production from macroalgae - İnan, Benan (Array, 2019)
In the last decade, studies that have focused on biodiesel production from algal biomass have been replaced with bioethanol production from algae, because bioethanol production from algae seems more promising when assessed on economic terms. Most coastal areas are covered with macroalgae, which are considered as a waste, and thus become a great problem for the municipality. Instead of their disposal, they can be alternatively utilized for bioethanol production. In this study, macroalgae located in the coastal regions of the Marmara Sea were collected and utilized for bioethanol production, and effects of the concentration of pre-treatment chemicals, pre-treatment temperature, and pre-treatment time on bioethanol yield were investigated. The highest bioethanol yields for dilute acid and alkaline pre-treatments were obtained under the conditions of 2 N sulfuric acid and 0.15 N potassium hydroxide solutions at the pre-treatment temperature of 100 °C and pre-treatment time of 60 minutes.